Influence of BMI in nephrolithiasis in an Appalachian pediatric population: A single-center experience. Issue 4 (August 2018) - Murphy, Margaret O.; Erpelding, Scott G.; Chishti, Aftab S.; Dugan, Adam; Ziada, Ali; Kiessling, Stefan G.
Summary: Introduction: The prevalence of pediatric nephrolithiasis has increased significantly in the past 20 years. Metabolic abnormalities predisposing adults to nephrolithiasis in obese patients include increased urinary sodium and uric acid excretion as well as low urine pH; however, limited data are available in the pediatric population. Objective: The aim was to investigate whether obese pediatric patients presenting with nephrolithiasis have a unique metabolic profile similar to reported findings in obese adults with nephrolithiasis. Study design: A retrospective chart review was performed in children aged 1–18 years seen at Kentucky Children's Hospital between 2010 and 2016. Inclusion criteria included all patients with documented stones confirmed by ultrasonography or computed tomography. Results: A total of 111 patient charts were reviewed in the study with a mean age of 11.8 ± 4.2 years. Seventy patients (63%) had a normal BMI and 41 patients (37%) were considered overweight/obese. There was no statistically significant relationship between BMI and stone recurrence. Obese patients had significantly decreased levels of urinary citrate, oxalate, magnesium, and potassium with significant elevations of urinary urea nitrogen, ammonia, and low urine pH compared with normal weight patients (Summary Figure). Discussion: Several groups have reported on metabolic findings within obese and non-obese pediatric patients. A Turkish study reported increased oxalate excretion and hypocitraturia in obese patients while a Korean study also reported increased rates of hypocitraturia in recurrent stone formers. Similar to these studies, we did find significant differences in citrate within our study population; however, we found significantly lower levels of urinary oxalate in obese patients. The majority of these studies do not report an association with BMI and urine pH although this has been reported in the adult population and our findings support an inverse relationship between body mass index (BMI) and pH. Our group found a higher level of calcium phosphate stones, supporting of Eisner's findings that high BMI is associated with increased supersaturation of calcium phosphate. Limitations of our study include being a single center and retrospective in nature. Conclusion: Our study demonstrates differences in types of stones and urinary metabolites in an obese pediatric population suggestive of different metabolic profiles contributing to stone disease. We report similar association between BMI and urine pH, urinary potassium, and citrate. This study confirmed our primary hypothesis that obese pediatric patients would have a different urinary mineral profile as evidenced by lower levels of citrate and potassium and low urine pH; however, obese patients did not exhibit significantly elevated urinary sodium and uric acid when normalized to weight, as described in the adult population. Our study did not confirm our secondary hypothesis that stone composition would be associated with BMI status or stone recurrence. Figure Urinary Parameters A) 24-hour urinary excretion of metabolites.  B) Supersaturation Index of Calcium Oxalate, Calcium Phosphate, and Uric Acid as well as urinary pH. Values are presented as medians with Mann–Whitney U test, Pearson chi-square test or Fisher exact test as appropriate. ∗ p <0.05.